EFEKTIVITAS EDUKASI BEYOND USE DATE SALEP KULIT DAN MATA TERHADAP TINGKAT PENGETAHUAN MASYARAKAT DESA PECANGAAN KULON - Apriliasari, Fiona; Eko Retnowati; Intan Adevia Rosnarita (Nusantara Hasana Journal, 2025)
Beyond Use Date (BUD) is the time limit for using a medication after the packaging is opened or after compounding is completed. Public understanding of BUD, especially for topical skin and eye ointments, remains low. This condition may decrease the effectiveness of treatment and increase the risk of side effects. The aim of this study was to compare the effectiveness of educational media leaflets and videos in improving public knowledge about BUD. This study used a quasi-experimental design with a pretest-posttest approach, involving three groups: leaflet, video, and control. A total of 366 respondents were selected using purposive sampling. The educational intervention was conducted over seven days, and knowledge was measured using a questionnaire that had been tested for validity and reliability. Data were analyzed using the Wilcoxon Signed Rank Test to assess changes in knowledge before and after the intervention, and the Mann-Whitney U Test to compare the effectiveness between media. The results show a significant increase in knowledge after the intervention, particularly in the leaflet group (61.50) and video group (60.50), while the control group shows a decrease (57.85). The Mann-Whitney U Test indicates that leaflets are more effective than videos (p = 0.000), with the highest mean rank found in the leaflet group (138.41). It can be concluded that education using leaflet media is more effective in increasing public knowledge about BUD, as it is easier to understand, can be read repeatedly, and allows direct interaction during health education sessions.